The Organization of Successful Education - Between Traditional and Modern Teaching - Požar, Hajnalka F. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
A number of reforms by the educational system have conditioned the changes in working methods and the attitude towards students. Modern teaching in schools of the 21st century was marked by the terms of flexibility and innovation, which requires the introduction of a number of innovations. Contemporary concepts of teaching arose from the need to increase the efficiency of teaching and to provide an organizational scheme where students have more freedom of movement and more diverse models of individual work and creation. The aim of our work is the research of didactic prerequisites for improving the teaching of health care. The paper analyses the prospect of utilizing different forms of work from the aspect of successfulness of education, for the improvement of teaching, as well as to overcome the traditional way of teaching. Special emphasis is placed on collaborative work, in which students work together, in pairs or in small groups. The positive effects of collaborative learning are reflected in a much faster and more lasting acquisition of knowledge and thought activity. Furthermore, the independence of students is increased, while critical and creative thinking is developed, along with communication and social skills. It encourages students to exchange experiences and to practice collaborative problem solving; therefore, the goals of individual students connect with the common goals.